Kesejahteraan Subjektif pada Anak yang Dibesarkan oleh Ibu Tunggal - Puspasari, Karisma Dewi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
A family is the fundamental unit crucial for individual development. The presence of a cohesive family structure significantly influences the subjective well-being of children. However, there is a growing number of families headed by single mothers, potentially impacting children's subjective well-being due to the absence of a paternal figure during their formative years. The aim of this study is to offer insights into the subjective well-being of children raised by single mothers. This research adopts a qualitative approach with a phenomenological design, utilizing in-depth interview techniques. The study involves 2 participants who were raised by single mothers. The findings reveal that both participants reported experiencing subjective well-being, attributed to social support from significant others. This support fosters positive affect and life satisfaction, which outweighs negative emotions, despite the absence of a father figure. The significance of this study lies in providing theoretical evidence that children raised by single mothers can indeed experience subjective well-being. Furthermore, these results serve as a foundation for developing interventions aimed at enhancing the subjective well-being of children raised by single mothers, through an analysis of the factors influencing well-being as identified in this study.